Penggunaan Metode Role-Playing Untuk Meningkatkan Minat Belajar Siswa Pada Materi Tokoh Islam Dalam Kemerdekaan Mata Pelajaran Sejarah Kebudayaan Islam di MA Nurul Huda Kelas 12 - Izdihara, Ihsan; Vauziah, Nur Aina; Puspita, Sinta; Sistri, Sistri (JURNAL MANAJEMEN PENDIDIKAN, 2025)
USING THE ROLE-PLAYING METHOD TO INCREASE STUDENTS' INTEREST IN LEARNING ABOUT ISLAMIC FIGURES IN INDEPENDENCE SUBJECTS HISTORY OF ISLAMIC CULTURE AT MA NURUL HUDA CLASS 12Abstract.  This study aims to determine the increase in student motivation and learning outcomes through the use of cooperative learning methods of Role Playing type on the material of Islamic Figures in Independence in the subject of Islamic Cultural History (SKI) in class XII MA Nurul Huda. This research uses a classroom action research (PTK) model consisting of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 30 grade XII students at MA Nurul Huda in the even semester of the 2024/2025 school year. Data collection techniques include interviews, observation, documentation, questionnaires, and written tests. The results showed that the application of the Role Playing method succeeded in increasing student learning motivation, which in cycle I reached 68% and increased 9% in cycle II to 76%. In addition, student learning outcomes also showed a significant increase, with an average score in cycle I of 67%, which increased by 8% to 75% in cycle II. These findings indicate that the Role Playing method is effective in increasing students' interest, motivation, and understanding of Islamic cultural history material, especially regarding Islamic figures in independence.